PEMANFAATAN PLATFORM MEDIA SOSIAL UNTUK USAHA MANDIRI PEMUDA BINA BUGIS SQUAD - TRISNIAN IFIANTI; Adi Adi; ENDANG SETIYO ASTUTI (Anfa Mediatama, 2023)
In the contemporary world, technological advancements have paved the way for online businesses to tap into a broader market using the internet and mobile devices. This implementation of Personal Knowledge Management (PKM) aims to achieve two primary objectives: firstly, training the